AI competency acquisition online? Engaging undergraduate students in an AI 101 Course through a chatbot workshop - MENKHOFF, Thomas (Institutional Knowledge at Singapore Management University, 2024)
In recent years, digital transformation has dominated industries at an unprecedented rate. Alongside the proliferation of Artificial ntelligence (AI) technologies in the workplace, institutions of higher learning are experiencing an unprecedented push to integrate AI into the education ecosystem (Popenici & Kerr, 2017; Renz & Hilbig, 2020). AI in education (AIED) has the propensity to enrich teaching and learning in higher education by personalising students’ learning courses, automating assessment tasks, or providing24/7 access to learning resources (Karandish, 2021). According to estimates by the AI Market in the US Education Report, the AIEDmarket will grow at a CAGR of 47.77% during the period 2018–2022 (Report, 2018). In this paper, we report on experiences during the implementation of an experiential chatbot workshop integrated into an introductory undergraduate management course on ‘Doing Business with AI.’ at Singapore Management University (SMU) that provides non-IT students with an opportunity to build a chatbot prototype using the ‘Dialogflow’ program. One basic premise is the assumption that such a novel, learning outcome-related, hands-on chatbot workshop motivates and engages learners provided its pedagogical approach is effective.